1944
DOI: 10.1128/jb.48.6.631-638.1944
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Resistance to Sulfonamides

Abstract: It has been known for some time that pantothenic acid is effective as a growth vitamin for many bacteria (Williams, 1943). The mechanism involved in the effect of pantothenic acid on growth is, however, not known. The present report deals with a study which indicates that pantothenic acid is involved in the synthesis of tryptophane essential for the multiplication of Staphylococcus aureus. Pantothenate alone or in combination with other vitamins likewise exercises a marked effect upon the resistance of staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1944
1944
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Both of these inhibitions are thought to be due to interference by the N' substituted portion of the sulfonamide molecule with a structurally similar part of a coenzyme molecule. Sevag and Green (1944) have shown that sulfonamides interfere with the metabolism of S. aureus by preventing the synthesis or utilization of the essential amino acid, tryptophane. Para-aminobenzoic acid (PABA) reverses the action of almost all of the sulfonamides and is thought to do so because of its structural similarity to the parent molecule, sulfanilamide.…”
mentioning
confidence: 99%
“…Both of these inhibitions are thought to be due to interference by the N' substituted portion of the sulfonamide molecule with a structurally similar part of a coenzyme molecule. Sevag and Green (1944) have shown that sulfonamides interfere with the metabolism of S. aureus by preventing the synthesis or utilization of the essential amino acid, tryptophane. Para-aminobenzoic acid (PABA) reverses the action of almost all of the sulfonamides and is thought to do so because of its structural similarity to the parent molecule, sulfanilamide.…”
mentioning
confidence: 99%
“…Five of the strains were sulfonamide-susceptible. The sulfonamide-resistant form of each of the strains had been obtained by growing the organisms in increasing concentrations of sulfathiazole (Sevag and Green, 1944).…”
mentioning
confidence: 99%
“…Flavoprotein dehydrogenases (riboflavin phosphoric acid proteins). Sevag and Green (1944) found that growth of certain strains of Staphylococcus aureus in the absence of added glucose is inhibited by sulfathiazole, and that this inhibition is antagonized by riboflavin. Atabrine has been shown by Haas (1944), working with isolated enzyme systems of yeast, to inhibit oxidation mediated by flavoprotein, and this inhibition is antagonized by the coenzyme (cf.…”
mentioning
confidence: 99%